Sostenibilidad del Programa de Apoyo a la Competitividad Productiva – PROCOMPITE, en la asociación Nuevo Amanecer Coari del distrito de Ilabaya, región Tacna del año 2020 al año 2022 - Muñoz Junes, Ismael Renato (2024)
This research focuses on analyzing the PROCOMPITE program, which has been created to improve the competitiveness and sustainability of productive chains and promote local and regional economic development; therefore, the relevance of adapting this initiative to new sectors as a strategic proposal to promote the implementation of projects for the benefit of rural communities in districts throughout Peru is observed. The general objective is to know the factors that contribute or limit the implementation of the intervention strategies of the PROCOMPITE Program in the district of Ilabaya, Tacna, during the years 2020 - 2022, through the analysis of the strategies that have been implemented in the process of perception of the partners and the actions implemented, to propose an improvement proposal to strengthen its implementation. Through the analysis of the data collected from program beneficiaries, municipality officials and those responsible for the PROCOMPITE program, the aspects that need to be aligned with the purpose of improving the program's implementation strategy have been evidenced. An improvement plan is proposed that seeks to satisfy the needs and empower the users of this public policy.